Guidelines for enhancing clinical supervision - Marthie C Bezuidenhout (AOSIS, 2003)
Clinical supervision is widely recognised as important and constructive in nursing and other health professions, but how is it actually done? Opsomming Kliniese toesighouding word as belangrik en konstruktief beskou in verpleging en ander gesondheidsberoepe, maar hoe word dit in werklikheid gedoen? *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.